Root growth, yield and NPK uptake of rice (Oryza sativa L.) varieties grown by system of rice intensification with varying planting geometry and weed management practices - Singh, Nain; Thenua, O.V.S.; Kumar, Dinesh; Tyagi, V.K. (Annals of Agricultural Research, 2014)
Field experiments were conducted for two years in sandy clay loam soil during kharif (rainy season) 2005 and 2006 at Indian Agricultural Research Institute, New Delhi to assess the root growth, yield and NPK uptake of aromatic rice varieties under varying weed management options and planting geometry. ’Pusa Sugandh 3’ and ’Pusa Sugandh 5’ varieties recorded statistically similar root dry weight at 0-15 cm soil depth, but both accumulated higher root dry weight than ’Pusa Basmati 1’. On an average, variety ’Pusa Sugandh 5’ produced 18.9% and 22.5% higher grain yield over ’Pusa Basmati 1’ and ’Pusa Sugandh 3’, respectively. Planting geometry 25 cm x 25 cm resulted in higher yield and NPK uptake than 30 cm x 30 cm. The varied planting geometry did not affect the NPK concentration in rice grain or straw significantly in either year of the study. The highest NPK concentration in rice grains and straw was estimated in weed free treatment, which in general, was significantly higher than both anilophos @ 0.4 kg/ha and weedy check. The highest NPK in grain + straw was removed by rice variety ’Pusa Sugandh 5’.